Early Cranioplasty is Associated with Greater Neurological Improvement: A Systematic Review and Meta‐Analysis. Issue 3 (14th August 2017) - Malcolm, James G.; Rindler, Rima S.; Chu, Jason K.; Chokshi, Falgun; Grossberg, Jonathan A.; Pradilla, Gustavo; Ahmad, Faiz U.
Abstract : BACKGROUND: Cranioplasty after decompressive craniectomy is a common neurosurgical procedure, yet the optimal timing of cranioplasty has not been well established. OBJECTIVE: To investigate whether the timing of cranioplasty is associated with differences in neurological outcome. METHODS: A systematic literature review and meta‐analysis was performed using MEDLINE, Scopus, and the Cochrane databases for studies reporting timing and neurological assessment for cranioplasty after decompressive craniectomy. Pre‐ and postcranioplasty neurological assessments for cranioplasty performed within (early) and beyond (late) 90 d were extracted. The standard mean difference (SMD) was used to normalize all neurological measures. Available datawere pooled to compare pre‐cranioplasty, postcranioplasty, and change in neurological status between early and late cranioplasty cohorts, and in the overall population. RESULTS: Eight retrospective observational studies were included for a total of 528 patients. Studies reported various outcome measures (eg, Barthel Index, Karnofsky Performance Scale, Functional Independence Measure, Glasgow Coma Scale, and Glasgow Outcome Score). Cranioplasty, regardless of timing, was associated with significant neurological improvement (SMD .56, P = .01). Comparing early and late cohorts, there was no difference in precranioplasty neurological baseline; however, postcranioplasty neurological outcome was significantly improved in the early cohort (SMD .58, P = .04) and showed greater magnitude of change (SMD 2.90, P = .02). CONCLUSION: Cranioplasty may improve neurological function, and earlier cranioplasty may enhance this effect. Future prospective studies evaluating long‐term, comprehensive neurological outcomes will be required to establish the true effect of cranioplasty on neurological outcome.